TRAP1 induced cisplatin resistance in gastric cancer cells by regulating oxidative stress - Ji, Zhenglei; Liu, Lu; Chen, Jingya; Zhu, Wanjing; Zhao, Yunli; Wu, Huazhang (Frontiers in Molecular Biosciences, 2025)
IntroductionGastric cancer (GC) is a common malignancy of digestive system with high morbidity and mortality. Cisplatin (CDDP) is often applied in GC clinical treatment, particularly in the postoperative adjuvant chemotherapy, where it improves patient survival and reduces recurrence risk. However, the development of drug resistance following prolonged use poses an obstacle in its clinical use. This study investigated the role of tumor necrosis factor receptor-associated protein 1 (TRAP1) in modulating the sensitivity of GC cells to CDDP through oxidative stress pathway.MethodsBioinformatic analysis was employed to assess TRAP1 expression in GC tissues compared to adjacent normal gastric tissues, and to evaluate its association with patient prognosis. Using lentivirus transfection and RNA interference, GC cell models with TRAP1 overexpression and silencing were established, then reactive oxygen species (ROS), mitochondrial membrane potential (MMP), DNA damage and cell death were measured following treatment with CDDP alone or in combination with antioxidant N-acetyl-L-cysteine (NAC).ResultsResults indicated that TRAP1 was upregulated in GC tissues and elevated TRAP1 was related with poor prognosis. In GC cells exposed to CDDP, TRAP1 reduced ROS, stabilized MMP and mitigated DNA damage, leading to diminished cell death. TRAP1 overexpression potentiated the protective effects of NAC, while TRAP1 silencing counteracted the protective effects.DiscussionThese findings indicated that TRAP1 attenuated CDDP sensitivity in GC cells by reducing cell death caused by CDDP-induced oxidative stress. TRAP1 represented a potential biomarker and a therapeutic target in GC treatment. This study provided a new strategy for improving the efficacy of CDDP-based chemotherapy through individualized treatment approaches.